Chemokines and Neurodegeneration in the Early Stage of Experimental Ischemic Stroke - Wolinski, Pawel; Glabinski, Andrzej (Mediators of Inflammation, 2013)
Neurodegeneration is a hallmark of most of the central nervous system (CNS) disorders including stroke. Recently inflammation has been implicated in pathogenesis of neurodegeneration and neurodegenerative diseases. The aim of this study was analysis of expression of several inflammatory markers and its correlation with development of neurodegeneration during the early stage of experimental stroke. Ischemic stroke model was induced by stereotaxic intracerebral injection of vasoconstricting agent endothelin-1 (ET-1). It was observed that neurodegeneration appears very early in that model and correlates well with migration of inflammatory lymphocytes and macrophages to the brain. Although the expression of several studied chemotactic cytokines (chemokines) was significantly increased at the early phase of ET-1 induced stroke model, no clear correlation of this expression with neurodegeneration was observed. These data may indicate that chemokines do not induce neurodegeneration directly. Upregulated in the ischemic brain chemokines may be a potential target for future therapies reducing inflammatory cell migration to the brain in early stroke. Inhibition of inflammatory cell accumulation in the brain at the early stage of stroke may lead to amelioration of ischemic neurodegeneration.